RIM-Binding Protein 2 Promotes a Large Number of CaV1.3 Ca2+-Channels and Contributes to Fast Synaptic Vesicle Replenishment at Hair Cell Active Zones - Krinner, Stefanie; Butola, Tanvi; Jung, SangYong; Wichmann, Carolin; Moser, Tobias (Frontiers in Cellular Neuroscience, 2017)
Ribbon synapses of inner hair cells mediate high rates of synchronous exocytosis to indefatigably track the stimulating sound with sub-millisecond precision. The sophisticated molecular machinery of the inner hair cell active zone realizes this impressive performance by enabling a large number of synaptic voltage-gated CaV1.3 Ca2+-channels, their tight coupling to synaptic vesicles and fast replenishment of fusion competent synaptic vesicles. Here we studied the role of RIM-binding protein 2 (RIM-BP2) – a multidomain cytomatrix protein known to directly interact with Rab3 interacting molecules (RIMs), Bassoon and CaV1.3 – that is present at the inner hair cell active zones. We combined confocal and stimulated emission depletion (STED) immunofluorescence microscopy, electron tomography, patch-clamp and confocal Ca2+-imaging, as well as auditory systems physiology to explore the morphological and functional effects of genetic RIM-BP2 disruption in constitutive RIM-BP2 knockout mice. We found that RIM-BP2 (1) positively regulates the number of synaptic CaV1.3 channels and thereby facilitates synaptic vesicle release and (2) supports fast synaptic vesicle recruitment after readily releasable pool depletion. However, Ca2+-influx – exocytosis coupling seemed unaltered for readily releasable synaptic vesicles. Recordings of auditory brainstem responses and of single auditory nerve fiber firing showed that RIM-BP2 disruption results in a mild deficit of synaptic sound encoding.